The Role of GHRM In Driving Green Work Engagement For Better Green Employee Performance - Gustiah , Indira puspa; Nurhayati, Mafizatun (Asean International Journal of Business, 2023)
Purpose: This study aims to determine and analyze the effect of green human resources management on green employee performance mediated by green work engagement in heavy equipment companies in Bekasi district. Methodology/approach: The method used in this research is descriptive quantitative method. The population in this study are all employees who work in heavy equipment companies in Jawa barat. With the structural equation modeling (SEM) analysis model, 110 samples were taken. The analysis technique in this study is Partial Least Square (PLS) using the smartPLS 3.0 program to test the hypothesis. Findings: The results showed that there was a positive and significant effect of green human resources management on green work engagement and green employee performance. There is an effect of green work engagement on green employee performance. Green work engagement can mediate the effect between green human resources management and green employee performance in heavy equipment companies in Bekasi distrct. Novelty/value: Green work engagement is very important to improve so that green employee performance can be further improved through efforts to implement green human resources management. Keywords: green human resources management, green work engagement, green employee performance.